2008
DOI: 10.1177/1099800408323219
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Job Stress and Urinary Cytokines in Healthy Nurses: A Cross-Sectional Study

Abstract: Cytokines such as angiogenin (ANG) and interleukin (IL-8) have been shown to be related to depressive symptoms and inflammatory diseases like coronary heart disease. They may thus be used as stress biomarkers to identify and prevent health problems. To investigate the relationship between cytokines and nurses' job-related stress, levels of urinary ANG and IL-8 were measured in healthy female hospital nurses in Japan. The level of job-related stress of the subjects was evaluated using the Nursing Stress Scale (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
(36 reference statements)
1
12
0
Order By: Relevance
“…For example, the low molecular weight of angiogenin permits its glomerular filtration and then its uptake by renal tubular cells or its clearance. In accordance with the above, angiogenin has been detected in the urine of healthy individuals (36). Thus, besides inflammation that increases angiogenin expression, impaired renal function may contribute to its accumulation.…”
Section: Discussionsupporting
confidence: 61%
“…For example, the low molecular weight of angiogenin permits its glomerular filtration and then its uptake by renal tubular cells or its clearance. In accordance with the above, angiogenin has been detected in the urine of healthy individuals (36). Thus, besides inflammation that increases angiogenin expression, impaired renal function may contribute to its accumulation.…”
Section: Discussionsupporting
confidence: 61%
“…Based on published POMS normative scores (total 14.8 to 20.3)[26], the VEG participants reported a more favorable mood state relative to OMN participants (0.10 ± 1.99 vs 15.33 ± 3.10 respectively, p = .007). Interestingly, recent investigations in healthy adult populations directly link POMS scores (range for mean population scores in these trials, 1.5 to 7.0) with markers of poor health outcomes including reduced flow-mediated dilation, metabolic syndrome, and job-related stress [29-31]. This interrelationship between health, mood, and diet patterns deserves further study.…”
Section: Discussionmentioning
confidence: 99%
“…Based on exploratory longitudinal study with repeated measures analysis, we found that nurses who experienced high levels of stress presented with lower levels of white blood cell (WBC) and tumor necrosis factor (TNF)-α, as well as higher levels of total salivary immunoglobulin A (sIgA) with statistical significance. Similarly, several studies were conducted to investigate the relationship between nurses’ job stress and immunological biomarkers ( 6 , 7 , 14 19 ). In observational studies exploring the job-related stress factors, nurses are considered to be one of the most appropriate subjects since (1) work-related stress level of nurses is relatively high; (2) job satisfaction is relatively lower than other occupational groups; and (3) recruitment of participants and data collection is more cooperative than other occupations.…”
Section: Introductionmentioning
confidence: 99%